A bottom‐up continuum approach of crystal plasticity for the analysis of fcc microwires under torsion. Issue 1 (18th November 2019) - Zoller, Kolja; Schulz, Katrin
Abstract: The microstructural evolution of face‐centered cubic microwires is studied using a physical motivated, homogenized continuum model of crystal plasticity. The dislocation configuration in the three‐dimensional space is thereby described via a Continuum Dislocation Dynamics (CDD) theory including a dislocation source term. The resulting spatial distribution of dislocation densities and strain components are shown for a relaxation problem with torsional loading.